AIDS, identity, and community : the HIV epidemic and lesbians and gay men - Greene, Beverly; Herek, Gregory M. (Sage Publications, 1995)
Hit hard by the AIDS epidemic in the United States and in much of Europe, the gay and lesbian community has been forced to examine existing notions of what it means to belong to a community based on sexual orientation. The editors of this second volume in the annual series on Psychological Perspectives on Lesbian and Gay Issues have collected a perceptive array of chapters that explore sexual behavior, personal identity, and community memberships of gay men and lesbian women. With the exception of a few, the chapters reflect study findings from AIDS-related research and include discussions of AIDS in large urban centers and in less populated settings outside of major AIDS epicenters. Focusing on underconsidered AIDS populations, the contributors explore specific topics concerning the AIDS epidemic among gay and bisexual men of color, lesbian women, and gay and lesbian youth.
"Sponsored by the Society for the Psychological Study of Lesbian and Gay Issues, Division 44 of the American Psychological Association."
Keywords: AIDS (Disease) -- Social aspects.; Gay people.; AIDS (Disease); Social ecology.; Homosexuality.; Male homosexuality.; Acquired Immunodeficiency Syndrome; Social Environment; Homosexuality; Homosexuality, Male; Sida -- Aspect social.; Personnes homosexuelles.; Sida.; Écologie sociale.; Homosexualité.; Homosexualité masculine.; male homosexuality.; human ecology.; homosexuality.; HEALTH & FITNESS -- Diseases -- AIDS & HIV.; MEDICAL -- AIDS & HIV.; Social ecology; AIDS (Disease) -- Social aspects; Gay people; Homosexualität; Aids; HIV.; Homoseksuelen.; Sociale identiteit.; AIDS -- Sociology